(untitled) (Singaporean Journal of Business Economics and Management, 2018)
Today, the increasing awareness among customers of their rights, changing demands and high competition requires constant progress in quality from the manufacturing firms. Thus, this study assessed the correlate between quality and price, profitability, market share and customer loyalty respectively of manufacturing firms in Rivers State, Nigeria. The study takes on the survey research process with the application of questionnaire to elicit data. The data from the questionnaire were analysed using mean scores, standard deviation and Pearson’s product moment correlation coefficient was used to ascertain the level of relationship between the research variables and structural equation model. The result showed that quality has strong positive influence on price, profitability, market share and customer loyalty respectively. Thus, we recommend that manufacturing firms should regularly review quality procedures and manufacturing processes of their products to adapt to customer’s changing requirements as to remain competitive in today’s dynamic business environment.